Highly soluble and thermally stable copolyimides modified with trifluoromethyl and siloxane. Issue 13 (3rd December 2014) - Yao, Pan; Gu, Junwei; Lei, Xingfeng; Sun, Wanlu; Chen, Ying; Zhang, Qiuyu
ABSTRACT A series of highly soluble aromatic polyimides with excellent thermal properties were fabricated by traditional two‐step polycondensation reaction of dianhydride monomer 4, 4′‐(4, 4′‐isopropylidenediphenoxy)bis(phthalic anhydride) or 4, 4‐(hexafluoroisopropylidene)diphthalic anhydride with diamine monomer 1, 3‐bis(4‐aminophenoxy)benzene or 1, 3‐bis(3‐aminopropyl) tetramethyldisiloxane in N, N‐dimethylacetylamide solvent. Results revealed that copolyimide of PI‐4 containing trifluoromethyl and tetramethyldisiloxane possessed excellent solubility and remarkable thermal properties. PI‐4 could dissolve well in common low boiling point solvents such as THF of up to 80 mg/mL and acetone of 40 mg/mL. Moreover, the 10% weight loss temperature of the PI‐4 was 539°C and the Tg value of the PI‐4 was 311°C. PI‐4 might be easily cast into flexible and tough films applied in optoelectronic devices. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41713.